RF transceiver‐based wireless pressure monitoring system. Issue 9 (27th June 2016) - Kumar, Amarjit; Pathak, Nagendra P.
ABSTRACT: This article reports the development and characterization of a robust RF transceiver system for wireless monitoring of the pressure variation in a gas pipeline installed in an industry. Proposed system consists of a monolithic silicon pressure sensor for converting applied pressure information to a DC voltage output, a varactor‐based voltage controlled oscillator (VCO) for converting DC voltages to RF signal, a power amplifier for amplifying the transmitting RF signal, and two wideband microstip fed filtering antennas used in transmitter and receiver modules. Transmitting antenna is used for radiating the selected RF signal (conditioned pressure information) while reflecting the undesired harmonics. Filtering antenna (Filtenna) at the receiver side is used to detect the desired RF signal while filtering out the undesired signal. Operating frequency band of proposed wireless pressure monitoring system is 2.2565–2.5804 GHz covering lower ISM band (2.4–2.5 GHz). As a proof of concept, experiment has been performed for monitoring of a pressure variation in the range 0–50 kPa and for a distance of 2 m between transmitting and receiving antennas. The measured pressure sensitivity of the proposed gas pressure monitoring system is 6.4786 MHz/kPa with a good linearity response. Calibration curve and curve fitting equations are provided for evaluating the pressure variation in a gas pipeline by detecting the received RF signal at the receiver end. Proposed system can be used for wirelessly monitoring the pressure of a gas pipeline installed in an industry. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2237–2242, 2016